Effect of Poor Glycemic Control with Length of Pulmonary Tuberculosis Treatment in Type 2 Diabetes Mellitus Patients - Widihastuti, Anastasya; Sirait, Robert Hotman; Simatupang, Abraham; Idhayu, Adeputri Tanesha (Indonesian Journal of Clinical Pharmacy, 2023)
Type 2 Diabetes Mellitus (T2DM) is one of the leading risk factors in developing Pulmonary Tuberculosis (PTB) and associated with a higher risk in recurrence, treatment failure, and MDR-TB. Duration of PTB treatment usually takes six months with first line regimen, however in uncontrolled blood glucose confirmed by HbA1c, Fasting Blood Glucose (FBG), and Postprandial Glucose (PPG) the treatment takes longer than usual because of the difficulty to achieve an optimal management in both diseases. The aim of this study was to assess the correlation between glycemic control and duration of anti-tuberculosis treatment at Persahabatan General Hospital, Jakarta in 2019-2021. It was a non-experimental study with analytical observational design and retrospective approach by using medical records. Data were analyzed descriptively and by the chi square method. Odds ratio and relative risk measure the association between duration of treatment in PTB patients and their gylcemic controls. The results showed that 57 PTB patients with T2DM (69.5%) received nine months course of anti-tuberculosis therapy. Most patients tend to have poor glycemic control shown by HbA1c level >7% (79.3%), FBG >130 mg/dL (72%), and PPG >180 mg/dL (80.5%). Correlation between glycemic control and duration of PTB treatment are significant shown by p-value result 0,001. The OR result was found to be 8.74 (95% CI 2.45-31.11) which indicate that patients with poor glycemic control have a greater risk to experience longer duration of PTB treatment. In conclusion, duration of PTB treatment are mostly done in more than six months due to poor glycemic control.